Nano-cellulose Reinforced Glass Ionomer Restorations: An In Vitro study - Najmeh Mohammadi; Zahra Fattah; Lida Vaziri Borazjani (Elsevier, 2023)
Objective: Various modifications in formulation of glass ionomer cements (GICs) have been made in order to improve the clinical performance of these restorations. The aim of this work was to evaluate the microleakage and microshear bond strength (μSBS) of bacterial cellulose nanocrystal (BCNC)-modified glass ionomer cement (GIC) restorations in primary dentition. Methods: A total number of 60 freshly extracted primary molar teeth were selected. Half of the samples were used for μSBS testing (in 2 groups, n = 15). In group 1, conventional GIC (CGIC) of Fuji IX (GC) was placed in cylindrical molds on dentinal surfaces. In group 2, CGIC of Fuji IX containing 1% wt of BCNCs was used. μSBS was evaluated using a universal testing machine. In another part of the study, microleakage of class V restorations was assessed according to the mentioned groups (n = 15). The sectioned samples were observed under stereomicroscope, and microleakage scores were recorded. SPSS version 16.0 (SPSS), independent samples t test, and Mann-Whitney U test were used for statistical analysis at a significance level of P < .05. Results: Results showed statistically significant differences between the μSBS of CGIC and modified GIC groups (P < .0001). The BCNC-modified GIC group recorded significantly higher bond strength values (3.51 ± 0.033 vs 1.38 ± 0.034 MPa). Also, microleakage scores of CGIC and BCNC-modified GIC restorations were not significantly different (P = .57). Conclusions: Based on our findings, it was concluded that incorporating BCNCs (1% wt) into the CGIC of Fuji IX significantly increased the μSBS to the dentin structure of the primary teeth.